Impact of China's Accession Protocol on its participation in the WTO dispute settlement mechanism: An analysis of eleven cases involving China's Accession Protocol - Sa Qianyi (Heliyon)
It has been twenty-three years since China acceded to the WTO. Since then, China has participated in high-profile disputes through the WTO's DSM. During this period, China has evolved from being a silent observer to a sophisticated participant in the DSM. This has provided a valuable opportunity to observe China's participation in the DSM and to analyse the factors affecting China's performance. This article examines China's engagement in the DSM relating to cases concerning China's Accession Protocol in which China was involved as a respondent. Based on an in-depth analysis of eleven Protocol-related cases settled among all cases pertaining to China's Accession Protocol, I conclude that both the Accession Protocol itself and the interpretive approach adopted by the DSB have made it challenging for China to defend against allegations of violating its obligations under China's Accession Protocol and the associated commitments outlined in China's Working Party Report. WTO Members can consequently without difficulty resort to certain provisions under China's Accession Protocol to bring cases against China.